2010
DOI: 10.1002/nbm.1607
|View full text |Cite
|
Sign up to set email alerts
|

Comparative determination of energy production rates and mitochondrial function using different 31P MRS quantitative methods in sedentary and trained subjects

Abstract: Muscle energetics has been largely and quantitatively investigated using (31)P MRS. Various methods have been used to estimate the corresponding rate of oxidative ATP synthesis (ATP(ox)); however, potential differences among methods have not been investigated. In this study, we aimed to compare the rates of ATP production and energy cost in two groups of subjects with different training status using four different methods: indirect method (method 1), ADP control model (method 2) and phosphate potential control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 88 publications
5
36
1
Order By: Relevance
“…Recently, Conley et al [3] also reported a coefficient of variation of 60 % for the ATP cost of contraction within a group of older individuals. Such variability between studies and among individuals is probably biological, rather than related to the method of quantification employed, as we recently demonstrated a close agreement between several 31 P-MRS approaches developed to estimate the ATP cost of contraction during dynamic exercise in humans [28]. In addition, it should be kept in mind that numerous muscles are involved in human locomotion and age-related alterations in muscle efficiency may vary among them.…”
Section: Evidence Of An Age-related Increase In the Atp Cost Of Contrmentioning
confidence: 81%
See 1 more Smart Citation
“…Recently, Conley et al [3] also reported a coefficient of variation of 60 % for the ATP cost of contraction within a group of older individuals. Such variability between studies and among individuals is probably biological, rather than related to the method of quantification employed, as we recently demonstrated a close agreement between several 31 P-MRS approaches developed to estimate the ATP cost of contraction during dynamic exercise in humans [28]. In addition, it should be kept in mind that numerous muscles are involved in human locomotion and age-related alterations in muscle efficiency may vary among them.…”
Section: Evidence Of An Age-related Increase In the Atp Cost Of Contrmentioning
confidence: 81%
“…At the onset of exercise, ATP generated from oxidative pathways is negligible such that anaerobic ATP synthesis accounts for the entire ATP synthesis [14]. The corresponding amount of ATP scaled to power output provides a reliable estimation of the initial rate of total ATP synthesis [27,28].…”
Section: Characteristicmentioning
confidence: 99%
“…peripheral arterial disease (PAD)5, 6, 7). These observations, together with the fact that evaluation of muscle oxidative metabolism provides insight into personal training status,8, 9 have led to a considerable methodological development in medical imaging for non‐invasive assessment of muscle energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Total ATP synthesis generated from aerobic and anaerobic pathways was scaled to the power output (in W) from the leg investigated by the MR coil. Methodological considerations addressing the validity and the reproducibility of the calculation of ATP synthesis rates have been previously addressed by us and others (25,29,31,33,38,39). The ratio of the rate of oxidative ATP synthesis to V O2p was also calculated as an index of mitochondrial efficiency (ATP/V O2).…”
Section: P-mrsmentioning
confidence: 99%
“…Consequently, it has actually been assayed very rarely in humans and only in resting muscle (1,46). Interestingly, we recently developed an experimental setup allowing the simultaneous measurement of pulmonary V O 2 (V O 2p ) (7) and oxidative ATP synthesis rate during knee-extension exercise (38) that can shed some light on mitochondrial efficiency in exercising muscle.…”
mentioning
confidence: 99%